Method for constructing vanadium-carbon composite coating layer on surface of lithium iron phosphate based on spray drying
By constructing a vanadium-carbon composite clad layer on the surface of the lithium iron phosphate positive electrode material, the problem of low electrochemical performance of the existing carbon-coated lithium iron phosphate material is solved, and significantly improved rate performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202411875851.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing carbon-coated lithium iron phosphate materials have shortcomings in electrochemical properties, especially in terms of rate discharge performance and cycle stability.
A vanadium-carbon composite clad layer is constructed on the surface of the iron phosphate precursor by spray drying. Through the coordinated optimization of vanadium-based phosphate and carbon layer, the efficiency of the charge-mass transfer process is improved.
The rate performance and cycle stability of lithium iron phosphate positive electrode material were significantly improved. The 1C discharge specific capacity reached 150.8mAh/g, the 10C discharge specific capacity reached 117.7mAh/g, and the capacity retention rate reached 94.5% after 1000 cycles.
Smart Images

Figure CN119695113A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a lithium iron phosphate positive electrode material for a lithium ion battery, and in particular to a method for constructing a material composite coating layer. Background Art
[0002] As a secondary battery positive electrode material, lithium iron phosphate has become the highest installed capacity lithium-ion battery positive electrode material due to its low cost, wide source of raw materials, and excellent safety performance. Among the various synthesis processes of lithium iron phosphate, the carbon thermal reduction method has become an important one-step synthesis method due to its simple process and easy process control. This process does not need to worry about the oxidation of raw materials during processing, and can use a variety of methods to process the raw materials to achieve the desired dispersion state.
[0003] The carbon thermal reduction method mainly includes two process routes: the red iron oxide route and the iron phosphate route. The final product prepared by the red iron oxide route has a higher rate discharge performance, but its capacity performance is relatively general; the iron phosphate route has the main advantages of higher capacity and the raw materials are not easy to absorb moisture and deliquesce. However, the physical properties of lithium iron phosphate positive electrode materials such as particle size distribution and particle morphology are largely inherited from the iron phosphate precursor, and these parameters directly affect the electrochemical properties of lithium iron phosphate. Due to the inheritance of physical properties between lithium iron phosphate and iron phosphate precursors, the performance of lithium iron phosphate is difficult to further improve under the established carbon thermal reduction process conditions. On the other hand, traditional carbon-coated lithium iron phosphate can improve the conductivity of the material, but cannot solve the problem of low intrinsic diffusion rate of lithium ions in the material, and the discharge capacity at higher rates is not ideal. Summary of the invention
[0004] The present invention is to solve the technical problem of low electrochemical performance of existing carbon-coated lithium iron phosphate, and provide a method for constructing a vanadium-carbon composite coating on the surface of lithium iron phosphate based on spray drying, which is a method for preparing lithium iron phosphate by optimizing the carbon thermal reduction process of the iron phosphate method, and by coating the surface of the iron phosphate precursor with vanadium, a vanadium-carbon composite coating on the surface of the lithium iron phosphate is constructed to improve its electrochemical performance. Specifically, the present invention uses a spray drying method to coat the surface of the iron phosphate precursor with vanadium-based phosphate, so that the modified iron phosphate precursor can generate a vanadium-carbon composite coating that synergistically optimizes the charge-mass transfer process during the carbon thermal reduction process. This method can not only effectively improve the rate discharge performance and cycle stability of lithium iron phosphate, but also achieve performance optimization without adjusting the existing process equipment.
[0005] The method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying of the present invention is carried out according to the following steps:
[0006] 1. Add a vanadium source, a phosphorus source, and an organic acid into pure water at a temperature of 50 to 95° C., and stir for 5 to 30 minutes at this temperature to dissolve, to obtain a clear solution with a pH value of ≥6.5; wherein the organic acid is one or a combination of acetic acid, citric acid, oxalic acid, ascorbic acid, and tartaric acid; in this step, the pH value of the solution is controlled to be ≥6.5 to ensure that iron phosphate is insoluble in the solution; at the same time, the mixing and dissolution of the reaction raw materials are accelerated under the condition of 50 to 95° C., and the complexation reaction and reduction reaction of the vanadium source are promoted;
[0007] 2. Add anhydrous iron phosphate crystalline powder to the mixed solution obtained in step 1 at a molar ratio of anhydrous iron phosphate to the vanadium source in step 1 of (15-500):1, and stir to uniformly disperse the iron phosphate powder in the mixed solution to obtain a dispersion;
[0008] 3. Transfer the dispersion to a spray dryer and perform spray drying at an outlet air temperature of 105-130° C. and a creeping speed of 10-30 RPM to obtain a vanadium-coated iron phosphate precursor powder. This step is a vanadium coating and rapid drying process, in which a layer of vanadium-based phosphate is coated on the surface of the iron phosphate while rapidly removing moisture.
[0009] 4. The molar ratio of the lithium source to the anhydrous iron phosphate in step 2 is (0.9-1.3):1, and the mass ratio of the carbon source in terms of carbon to the anhydrous iron phosphate in step 2 is (5-20):1. After the lithium source, the carbon source and the vanadium-coated iron phosphate precursor powder are evenly mixed, the temperature is increased to 550-800°C at a heating rate of 2-10°C / min under an inert atmosphere and maintained for 2-12 hours for calcination. Under this condition, the carbon source is fully pyrolyzed and the carbon thermal reduction reaction is fully carried out. The temperature is cooled to room temperature to obtain a lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer on the surface.
[0010] Furthermore, the vanadium source in step 1 is one or a mixture of ammonium metavanadate, lithium metavanadate, and vanadium pentoxide.
[0011] Furthermore, the phosphorus source described in step 1 is one or a mixture of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and lithium phosphate;
[0012] Furthermore, the molar ratio of the vanadium source, phosphorus source and organic acid in step 1 is (0.5-3):(1-5):(0.5-5).
[0013] Furthermore, the concentration of the V element in the solution in step 1 is 0.4-4 mmol / L.
[0014] Furthermore, the molar ratio of the anhydrous ferric phosphate in step 2 to the vanadium source in step 1 is (35-400):1.
[0015] Furthermore, the lithium source in step 4 is one or a mixture of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium dihydrogen phosphate;
[0016] Furthermore, the carbon source in step 4 is one or a mixture of several of glucose, sucrose, citric acid, oxalic acid, ascorbic acid, polyacrylonitrile, and phenolic resin.
[0017] Furthermore, the precursor, lithium source and carbon source in step 4 are preferably mixed by manual grinding with a mortar and pestle, or ball milling with a ball mill, or sand milling with a sand mill, or one or more of a three-dimensional mixer, a V-shaped mixer and a ribbon mixer. The purpose is to improve the uniformity of the mixing of the reaction raw materials, thereby improving the contact of the solid phase reaction, so as to improve the purity of the sintered product and shorten the reaction time.
[0018] Furthermore, the inert gas in step 4 is argon, nitrogen or a hydrogen-argon mixture.
[0019] The beneficial effects of the present invention compared with the prior art are:
[0020] (1) The present invention uses a technology combining spray drying and carbon thermal reduction. First, the iron phosphate precursor is subjected to vanadium coating modification by spray drying, and then a vanadium-carbon composite coating structure is formed on the surface of the lithium iron phosphate by a carbon thermal reduction process. Compared with the conventional lithium iron phosphate coated carbon shell, the vanadium-carbon composite coating constructed by the present invention comprehensively utilizes the advantages of high electronic conductivity of the carbon layer and high ion diffusion rate of the vanadium-based material, and synergistically promotes charge transfer and ion diffusion. The prepared material has a specific capacity of 150.8mAh / g at a 1C discharge rate and a specific capacity of 117.7mAh / g at a 10C discharge rate; while the lithium iron phosphate prepared in the comparative example has a 1C discharge specific capacity of 138.6mAh / g and a 10C discharge specific capacity of 94.0mAh / g. Thanks to the optimization of the charge-mass transfer of the lithium iron phosphate positive electrode material by the vanadium-carbon composite coating layer, the vanadium-carbon composite coated lithium iron phosphate positive electrode material synthesized by the present invention has a capacity retention rate of 94.5% after 1C / 1C constant current charge and discharge cycles for 1000 times; while the capacity retention rate of the comparative example under this condition is 82.7%. Obviously, the vanadium-based phosphate-coated iron phosphate precursor prepared by the present invention, which is constructed with a vanadium-carbon composite coating layer through a carbothermal reduction process, significantly improves the cycle performance and rate performance of the lithium iron phosphate positive electrode material.
[0021] (2) The present invention utilizes a spray drying method to perform vanadium coating modification on an iron phosphate precursor, and the obtained vanadium-based phosphate-coated iron phosphate precursor has good process compatibility. Since the precursor after vanadium coating still has similar morphology, particle size and other physical properties as the ordinary iron phosphate precursor, in the subsequent carbon thermal reduction process, there is no need to add new equipment or change the type and mixing method of the lithium source and carbon source. It is only necessary to appropriately adjust the amount of lithium source and carbon source added to meet the lithium matching requirements of vanadium, and make full use of the organic acid that dissolves vanadium as part of the carbon source to construct a vanadium-carbon composite coating layer, which significantly improves the electrochemical performance of the lithium iron phosphate positive electrode material. The present invention is fully compatible with the existing iron phosphate carbon thermal reduction process, and effectively improves the economic benefits of the iron phosphate precursor and the lithium iron phosphate positive electrode material.
[0022] (3) The raw materials required for the preparation method of the present invention are widely available, low in cost, and simple in process flow. The product has high reproducibility and can be produced in large quantities at one time, thus meeting the needs of practical applications of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 X-ray diffraction patterns of lithium iron phosphate, a positive electrode material for lithium-ion batteries prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0024] Figure 2 This is a scanning electron microscope image of the vanadium-coated iron phosphate precursor powder prepared in Example 1;
[0025] Figure 3 Element distribution diagram of the vanadium-coated iron phosphate precursor powder prepared in Example 1;
[0026] Figure 4 This is a scanning electron microscope image of the iron phosphate precursor powder described in Comparative Example 1;
[0027] Figure 5 Element distribution diagram of the iron phosphate precursor powder described in Comparative Example 1;
[0028] Figure 6 This is a scanning electron microscope image of the vanadium-carbon composite coated lithium iron phosphate positive electrode material prepared in Example 1;
[0029] Figure 7 This is the element distribution diagram of the vanadium-carbon composite coated lithium iron phosphate positive electrode material prepared in Example 1;
[0030] Figure 8 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material prepared in Comparative Example 1;
[0031] Fig. 9 Element distribution diagram of the lithium iron phosphate positive electrode material prepared in Comparative Example 1;
[0032] Fig.10 This is a transmission electron microscope image of a lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer prepared in Example 1.
[0033] Fig.11 The rate performance diagram of vanadium-carbon composite coated lithium iron phosphate and lithium iron phosphate prepared as the positive electrode materials of lithium ion batteries in Example 1 and Comparative Example 1;
[0034] Fig.12 The cycle performance diagram of the lithium-ion battery positive electrode materials vanadium-carbon composite coated lithium iron phosphate and lithium iron phosphate prepared in Example 1 and Comparative Example 1 under 1C / 1C charge and discharge cycle. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0036] Example 1: The method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying in this example is carried out according to the following steps:
[0037] 1. Weigh 0.25g of vanadium pentoxide, 0.48g of ammonium dihydrogen phosphate, and 0.37g of oxalic acid, stir and dissolve in 1L of pure water, heat to 90°C and stir until the raw materials are dissolved to obtain a clear solution; the concentration of V element in the solution is 2.8mmol / L, and the pH value of the solution is 6.5. Under this condition, iron phosphate will not dissolve in the solution; the condition of 90°C will accelerate the mixing and dissolution of the reaction raw materials, and promote the complexation reaction and reduction reaction of the vanadium source;
[0038] 2. Weigh 8.14 g of iron phosphate powder, add it to the clear solution obtained in step 1, and stir for 15 minutes to evenly disperse the iron phosphate powder in the mixed solution to obtain a dispersion;
[0039] 3. Transfer the dispersion to the spray dryer at an outlet temperature of 120°C, a peristaltic pump feed speed of 20RPM, and a wind speed of 40.0m 3 / min, spray drying was performed to obtain a light yellow-green vanadium-coated iron phosphate precursor powder; this step is a vanadium coating and rapid drying process, and a layer of vanadium-based phosphate is coated on the surface of the iron phosphate while water is rapidly removed;
[0040] 4. Grind 5.00g of vanadium-coated iron phosphate precursor powder, 1.16g of lithium carbonate and 0.72g of glucose in a planetary ball mill at a speed of 1000RPM and a ball-to-material mass ratio of 20:1 for 9 hours using dry grinding to obtain a mixed powder; then transfer the mixed powder to a tubular furnace, and under the protection of a flowing argon atmosphere, raise the temperature to 650°C at a heating rate of 5°C / min and calcine for 9 hours. After natural cooling, a lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer on the surface is obtained.
[0041] Comparative Example 1: In this comparative example, lithium iron phosphate is prepared by carbon thermal reduction of an iron phosphate precursor that has not been subjected to vanadium coating treatment. The specific preparation method is as follows:
[0042] 1. Weigh 5.00 g of iron phosphate, 1.22 g of lithium carbonate, and 0.82 g of glucose and add them into a planetary ball mill. Mill for 9 h at a ball mill speed of 1000 RPM and a ball-to-material ratio of 20:1. Grind in a dry grinding manner to obtain a mixed powder.
[0043] Second, the mixed powder was transferred to a tube furnace, and under the protection of flowing argon atmosphere, the temperature was raised to 650℃ at a rate of 5℃ / min and maintained for 9 hours for calcination. After natural cooling, lithium iron phosphate positive electrode material was obtained. This is a synthesis of lithium iron phosphate by carbon thermal reduction of iron phosphate precursor without vanadium coating.
[0044] The carbon-coated lithium iron phosphate positive electrode material obtained in Comparative Example 1 was used as the active material, Super P was used as the conductive agent, and PVDF was used as the binder. The materials were mixed with paste at a mass ratio of 8:1:1 to obtain a positive electrode slurry. The slurry was coated on an aluminum foil, dried, and cut into positive electrode sheets with a diameter of 14 mm. Finally, a half-cell was assembled and the positive electrode sheet was tested at 2.5-4.2V (vs. Li + / Li) in the voltage range. The results show that at 1C rate, its discharge capacity is 138.6mAh / g, and the capacity retention rate after 1000 cycles is 82.7%. At 10C rate, its discharge capacity is 94.0mAh / g.
[0045] Comparative Example 2: The method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying in this comparative example is carried out according to the following steps:
[0046] 1. Weigh 1.01g vanadium pentoxide, 1.91g ammonium dihydrogen phosphate, and 1.50g oxalic acid, stir and dissolve in 1L pure water, and keep heating at 90°C and stirring until a clear solution is obtained; the concentration of V element in the solution in this step is 11.1mmol / L;
[0047] 2. Weigh 8.14 g of iron phosphate and add it to the clear solution obtained in step 1. Stir for 15 minutes to evenly disperse the iron phosphate powder to obtain a dispersion;
[0048] 3. Put the dispersion into the spray dryer at an outlet temperature of 120°C, a peristaltic pump feed speed of 20RPM, and a wind speed of 40.0m 3 The powder was spray-dried at 400 °C / min to obtain a light yellow-green vanadium-coated iron phosphate precursor powder.
[0049] 4. 5.00 g of vanadium-coated iron phosphate precursor powder, 1.03 g of lithium carbonate, and 0.52 g of glucose were ball-milled in a planetary ball mill at a rotation speed of 1000 RPM and a ball-to-material ratio of 20:1 for 9 hours. The grinding method was dry grinding to obtain a mixed powder; the mixed powder was transferred to a tubular furnace, and under the protection of a flowing argon atmosphere, the temperature was raised to 650°C at a heating rate of 5°C / min and calcined for 9 hours. After natural cooling, a vanadium-carbon composite coated lithium iron phosphate positive electrode material was obtained.
[0050] The lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer obtained in Comparative Example 2 was used as the active material, Super P was used as the conductive agent, and PVDF was used as the binder. The materials were mixed with a paste at a mass ratio of 8:1:1 to obtain a positive electrode slurry. The slurry was coated on an aluminum foil, dried, and cut into positive electrode sheets with a diameter of 14 mm. Finally, a half-cell was assembled and the positive electrode sheet was tested at 2.5-4.2V (vs. Li + / Li) in the voltage range. The results show that at 1C rate, its discharge capacity is 120.3mAh / g; at 10C rate, its discharge capacity is 51.0mAh / g.
[0051] Figure 1 The X-ray diffraction patterns of lithium iron phosphate, a positive electrode material for lithium-ion batteries, prepared in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 1 It can be seen that the samples of Example 1 and Comparative Example 1 both show characteristic diffraction peaks of lithium iron phosphate LiFePO4; while Comparative Example 2 shows a mixed diffraction peak of lithium iron phosphate LiFePO4 and vanadium-based phosphate, which is caused by excessive addition of vanadium in Comparative Example 2.
[0052] Figure 2 This is a scanning electron microscope image of the vanadium-coated iron phosphate precursor powder prepared in Example 1. It can be observed that after spray drying, the vanadium source, phosphorus source and organic acid are coated on the surface of the agglomerated particles, and the spray drying step does not significantly change the primary particle size and distribution state.
[0053] Figure 3This is the element distribution diagram of the vanadium-coated iron phosphate precursor powder prepared in step 3 of Example 1. It can be observed that the vanadium element is evenly distributed in the agglomerated particles without obvious vacancies or concentrated areas, indicating that the vanadium source is evenly coated on the particle surface.
[0054] Figure 4 This is a scanning electron microscope image of the iron phosphate precursor powder described in Comparative Example 1. The precursor is a battery-grade anhydrous iron phosphate powder and is used as the substrate for vanadium coating treatment in Example 1, Example 2 and Comparative Example 1.
[0055] Figure 5 : is the element distribution diagram of the iron phosphate precursor powder described in Comparative Example 1. It can be observed that the iron phosphate precursor described in Comparative Example 1 does not contain vanadium element.
[0056] Figure 6 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer prepared in Example 1. It can be seen from the figure that the vanadium-carbon composite coating layer has no significant effect on the morphology, size and particle size distribution of the lithium iron phosphate primary particles.
[0057] Figure 7 This is an element distribution diagram of the lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer prepared in Example 1. It can be observed that at the agglomerated particles, the distribution of vanadium elements has no vacancies or dense areas, indicating that vanadium is uniformly coated on the surface of the lithium iron phosphate positive electrode material.
[0058] Figure 8 This is a scanning electron microscope image of the lithium iron phosphate cathode material prepared in Comparative Example 1. It can be seen that its morphological characteristics conform to the typical characteristics of the carbon-coated lithium iron phosphate cathode material prepared by the iron phosphate method carbothermal reduction process.
[0059] Fig. 9 This is an element distribution diagram of the lithium iron phosphate positive electrode material prepared in Comparative Example 1. It can be observed that the carbon-coated lithium iron phosphate positive electrode material prepared in Comparative Example 1 does not contain vanadium.
[0060] Fig.10 This is a transmission electron microscope image of the lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer prepared in Example 1. It can be seen that the vanadium layer Li3V2(PO4)3 and the carbon layer C are coated on the outside of the LiFePO4 particle phase, which directly proves the existence of the vanadium-carbon composite coating layer constructed in the lithium iron phosphate positive electrode material prepared in Example 1.
[0061] The lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer prepared in Example 1 and the carbon-coated lithium iron phosphate prepared in Comparative Example 1 were used as active materials, Super P was used as a conductive agent, and PVDF was used as a binder. They were mixed with a paste at a mass ratio of 8:1:1 to obtain a positive electrode slurry. The slurry was coated on an aluminum foil, dried, and cut into positive electrode sheets with a diameter of 14 mm. Finally, a half-cell was assembled and the positive electrode was charged at 2.5-4.2V (vs. Li + / Li) voltage range for charge and discharge tests.
[0062] Fig.11 The rate performance diagram of the vanadium-carbon composite coated lithium iron phosphate and carbon coated lithium iron phosphate prepared for lithium ion battery positive electrode materials in Example 1 and Comparative Example 1. At 1C and 10C rates, the discharge capacity of the vanadium-carbon composite coated lithium iron phosphate positive electrode material prepared in Example 1 reached 150.8mAh / g and 117.7mAh / g; the carbon coated lithium iron phosphate positive electrode material prepared in Comparative Example 1 under the same carbon thermal reduction process conditions had a discharge capacity of only 138.6mAh / g and 94.0mAh / g at 1C and 10C rates. This shows that the vanadium-carbon composite coating layer constructed based on spray drying has a significant improvement in the rate performance of the lithium iron phosphate positive electrode material.
[0063] Fig.12 The cycle performance diagram of the lithium-ion battery positive electrode materials vanadium-carbon composite coated lithium iron phosphate and carbon coated lithium iron phosphate prepared in Example 1 and Comparative Example 1. + After 1000 cycles in the voltage range of 1.5V / Li), the capacity retention rate of the vanadium-carbon composite coated lithium iron phosphate positive electrode material prepared in Example 1 is 94.5%, and the capacity retention rate of the carbon-coated lithium iron phosphate positive electrode material prepared in Comparative Example 1 is 82.7%. This indicates that the vanadium-carbon composite coating layer constructed based on spray drying has a significant effect on improving the cycle performance of the lithium iron phosphate positive electrode material.
[0064] Example 2: The method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying in this example is carried out according to the following steps:
[0065] 1. Weigh 0.03g of vanadium pentoxide, 0.05g of ammonium dihydrogen phosphate, and 0.04g of oxalic acid, stir and dissolve in 1L of pure water, heat to 90°C and stir until the raw materials are dissolved to obtain a clear solution; the concentration of V element in the solution is 0.3mmol / L, and the pH value of the solution is 6.5. Under this condition, iron phosphate will not dissolve in the solution; the condition of 90°C will accelerate the mixing and dissolution of the reaction raw materials, and promote the complexation reaction and reduction reaction of the vanadium source;
[0066] 2. Weigh 8.14 g of iron phosphate powder, add it to the clear solution obtained in step 1, and stir for 15 minutes to evenly disperse the iron phosphate powder in the mixed solution to obtain a dispersion;
[0067] 3. Transfer the dispersion to the spray dryer at an outlet temperature of 120°C, a peristaltic pump feed speed of 20RPM, and a wind speed of 40.0m 3 / min, spray drying was performed to obtain a light yellow-green vanadium-coated iron phosphate precursor powder; this step is a vanadium coating and rapid drying process, and a layer of vanadium-based phosphate is coated on the surface of the iron phosphate while water is rapidly removed;
[0068] 4. Grind 5.00 g of vanadium-coated iron phosphate precursor powder, 1.22 g of lithium carbonate and 0.80 g of glucose in a planetary ball mill at a speed of 1000 RPM and a ball-to-material mass ratio of 20:1 for 9 hours using dry grinding to obtain a mixed powder; then transfer the mixed powder to a tubular furnace, and under the protection of a flowing argon atmosphere, raise the temperature to 650°C at a heating rate of 5°C / min and calcine for 9 hours. After natural cooling, a lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer on the surface is obtained.
[0069] The lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer on the surface prepared in Example 2 was used as the active material, Super P was used as the conductive agent, and PVDF was used as the binder. The materials were mixed with a paste at a mass ratio of 8:1:1 to obtain a positive electrode slurry. The slurry was coated on an aluminum foil, dried, and cut into positive electrode sheets with a diameter of 14 mm. Finally, a half-cell was assembled and the positive electrode was tested at 2.5-4.2 V (vs. Li + / Li) voltage range. The results show that at a 1C rate, its discharge capacity is 145.8mAh / g.
[0070] The present invention combines spray drying with carbon thermal reduction, optimizes and modifies the iron phosphate precursor by coating with vanadium-based phosphate, and then constructs a vanadium-carbon composite coating layer that optimizes charge-mass transfer through a carbon thermal reduction reaction, combines the high electronic conductivity of the carbon layer and the high ion diffusion rate advantages of the vanadium-based material, and synergistically optimizes the transfer process of electrons and ions, significantly improving the rate performance and cycle stability of the prepared lithium iron phosphate, thereby achieving the overall optimization of the carbon thermal reduction process of the iron phosphate method. The vanadium-carbon composite coated lithium iron phosphate positive electrode material prepared by the present invention exhibits excellent specific capacity at various discharge rates, and has a high capacity retention rate in long-term charge and discharge cycles. In addition, the method of the present invention has good process compatibility, does not require additional equipment or changes in existing processes, and only needs to appropriately regulate the amount of lithium source and carbon source added to achieve performance improvement. The raw materials used are low in cost and wide in source, the process flow is simple, the product reproducibility is high, and it can be mass-produced.
Claims
1. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying, characterized in that The method proceeds as follows:
1. Add vanadium source, phosphorus source and organic acid into pure water at a temperature of 50-95°C, and stir for 5-30 minutes to dissolve at this temperature to obtain a clear solution with a pH value of ≥6.5; wherein the organic acid is one or a combination of acetic acid, citric acid, oxalic acid, ascorbic acid and tartaric acid; 2. Add anhydrous iron phosphate crystalline powder to the mixed solution obtained in step 1 at a molar ratio of anhydrous iron phosphate to the vanadium source in step 1 of (15-500):1, and stir to uniformly disperse the iron phosphate powder in the mixed solution to obtain a dispersion; 3. Transfer the dispersion to a spray dryer and perform spray drying at an outlet air temperature of 105 to 130° C. and a creeping speed of 10 to 30 RPM to obtain a vanadium-coated iron phosphate precursor powder; 4. The molar ratio of the lithium source to the anhydrous iron phosphate in step 2 is (0.9-1.3):1, and the mass ratio of the carbon source in terms of carbon to the anhydrous iron phosphate in step 2 is (5-20):
1. After the lithium source, the carbon source and the vanadium-coated iron phosphate precursor powder are evenly mixed, the temperature is increased to 550-800°C at a heating rate of 2-10°C / min under an inert atmosphere, and the mixture is kept for 2-12 hours for calcination, and then cooled to room temperature to obtain a lithium iron phosphate positive electrode material with a vanadium-carbon composite coating layer on the surface.
2. The method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1, characterized in that: The vanadium source described in step 1 is one or a mixture of ammonium metavanadate, lithium metavanadate, and vanadium pentoxide.
3. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The phosphorus source described in step 1 is one or a mixture of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and lithium phosphate.
4. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The molar ratio of the vanadium source, phosphorus source and organic acid in step 1 is (0.5-3):(1-5):(0.5-5).
5. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The concentration of the V element in the solution described in step 1 is 0.4-4 mmol / L.
6. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The lithium source described in step 4 is one or a mixture of lithium carbonate, lithium hydroxide, lithium nitrate, and lithium dihydrogen phosphate.
7. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The carbon source described in step 4 is one or a mixture of several of glucose, sucrose, citric acid, oxalic acid, ascorbic acid, polyacrylonitrile and phenolic resin.
8. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The precursor described in step 4 is preferably mixed with the lithium source and the carbon source by manual grinding with a mortar and pestle, or ball milling with a ball mill, or sand milling with a sand mill, or mixing with one or more of a three-dimensional mixer, a V-shaped mixer, and a ribbon mixer.
9. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The inert gas described in step 4 is argon, nitrogen or a mixture of hydrogen and argon.
10. A method for constructing a vanadium-carbon composite coating layer on the surface of lithium iron phosphate based on spray drying according to claim 1 or 2, characterized in that: The molar ratio of the anhydrous ferric phosphate in step 2 to the vanadium source in step 1 is (35-400):1.
Citation Information
Patent Citations
Lithium ion battery phosphatic composite cathode material and preparation method thereof
CN102244263A
Preparation method for positive electrode material--lithium iron phosphate
CN103165882A
Lithium ion battery positive electrode material and preparation method thereof, lithium ion battery positive electrode slurry and positive electrode, lithium ion battery and equipment
CN110783546A
Vanadium-doped carbon-coated lithium iron phosphate, preparation method and application thereof
CN112736226A
Lithium iron phosphate-lithium vanadium phosphate composite positive electrode material and preparation method and application thereof
CN114300661A